2015
DOI: 10.1021/cm504500a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Complex Stacking of Fully-Ordered Transition Metal Layers in Li4FeSbO6 Materials

Abstract: As part of a broad project to explore Li4MM′O6 materials (with M and M′ being selected from a wide variety of metals) as positive electrode materials for Li-ion batteries, the structures of Li4FeSbO6 materials with both stoichiometric and slightly deficient lithium contents are studied here. For lithium content varying from 3.8 to 4.0, the color changes from yellow to black and extra superstructure peaks are seen in the XRD patterns. These extra peaks appear as satellites around the four superstructure peaks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…demonstrated that the reversible capacity of Li 1+ x Fe y Mn 1− x − y O 2 is generated from the Fe 3+ /Fe 4+ redox couple at approximately 4 V, which was further confirmed by the 57 Fe Mössbauer spectrum . Tarascon and co‐workers also found that in Li 4 FeSbO 6 and Li 2 Ru 1‐ x Fe x O 3 , Fe 3+ can be oxidized to Fe 4+ , which was accompanied by the oxidation of O 2− to O 2 2− during delithiation. Although most observations verify the oxidation of Fe 3+ , a clear explanation of the redox mechanism for either Fe or O in the Ni‐, Fe‐, and Mn‐containing Li‐rich materials is still lacking.…”
Section: Introductionmentioning
confidence: 93%
“…demonstrated that the reversible capacity of Li 1+ x Fe y Mn 1− x − y O 2 is generated from the Fe 3+ /Fe 4+ redox couple at approximately 4 V, which was further confirmed by the 57 Fe Mössbauer spectrum . Tarascon and co‐workers also found that in Li 4 FeSbO 6 and Li 2 Ru 1‐ x Fe x O 3 , Fe 3+ can be oxidized to Fe 4+ , which was accompanied by the oxidation of O 2− to O 2 2− during delithiation. Although most observations verify the oxidation of Fe 3+ , a clear explanation of the redox mechanism for either Fe or O in the Ni‐, Fe‐, and Mn‐containing Li‐rich materials is still lacking.…”
Section: Introductionmentioning
confidence: 93%
“…A solid solution of Li 4 FeSbO 6 was investigated as a new cathode material, with oxygen‐release and oxygen‐redox occurring during charging and discharging. The limited reversibility of the oxygen redox was first presented and discussed in these investigations.…”
Section: Lithium‐rich Rock‐salt Oxidesmentioning
confidence: 99%
“…Li 2 Ru 0.75 Sn 0.25 O 3 was found to display highly reversible anionic redox, though 0.2 Li ions per formula still cannot be reinserted into the host due to partial oxygen loss in the first cycle. The lithium‐excess oxides Li 2 MoO 3 , Li 4 FeSbO 6 , and Y‐doped Li 6 ZrO 8 all display low Coulombic efficiency and involve anionic redox …”
Section: Anionic‐redox‐induced Effects On Electrochemical Performancementioning
confidence: 99%
“…Manganese-substituted Li 3 NbO 4 , Li 1.3 Nb 0.3 Mn 0.4 O 2 (0.43Li 3 NbO 4 –0.57LiMnO 2 ), delivers large reversible capacity (approximately 300 mAh g −1 ) with reversible solid-state redox reaction of oxide ions20. Similar to pentavalent niobium, a material with pentavalent antimony, Li 4 FeSbO 6 , has been recently reported25. Solid-state redox reaction of oxide ions is also activated in Li 4 FeSbO 6 , and a reductive coupling mechanism as an irreversible process has been evidenced in this system.…”
mentioning
confidence: 99%